Strategi Pemasaran Syariah Pada Aila Fashion Serba Tiga Puluh Lima Ribu Kecamatan Singaran Pati Kota Bengkulu - Anugraha jaya, Wahyu; Mursalin, Supardi; Makmur (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2023)
The purpose of this study was to determine the implementation of sharia marketing strategies at Aila Fashion Thirty-Five Thousand All-round Fashion in Bengkulu City. To test this, researchers used quantitative methods with primary data collection techniques in the form of interviews with 6 informants. The results showed that the implementation of the sharia marketing strategy at the Aila Fashion All-round 35000 Store in Bengkulu City was by creating attractive and reliable offers, providing excellent service, providing memorable value, offering an up to date business model, and building synergy with stakeholders. However, the implementation has not been fully implemented properly, because the Aila Fashion All-round 35000 Shop in Bengkulu City has not been able to provide maximum excellent service and the products offered seem old-fashioned and not the latest or up to date, while creating attractive offers provides impressive value. , and building synergy with stakeholders The Aila Fashion All-round 35000 Shop, Bengkulu City, has done well.